A Garnet‐Type Solid‐Electrolyte‐Based Molten Lithium−Molybdenum−Iron(II) Chloride Battery with Advanced Reaction Mechanism. Issue 32 (23rd June 2020) - Xu, Jing; Liu, Kai; Jin, Yang; Sun, Bin; Zhang, Zili; Chen, Yi; Su, Dawei; Wang, Guoxiu; Wu, Hui; Cui, Yi
Abstract: Solid‐electrolyte‐based molten‐metal batteries have attracted considerable attention for grid‐scale energy storage. Although ZEBRA batteries are considered one of the promising candidates, they still have the potential concern of metal particle growth and ion exchange with the β"‐Al2 O3 electrolyte. Herein, a Li6.4 La3 Zr1.4 Ta0.6 O12 solid‐electrolyte‐based molten lithium−molybdenum−iron(II) chloride battery (denoted as Li−Mo−FeCl2 ) operated at temperature of 250 °C, comprising a mixture of Fe and LiCl cathode materials, a Li anode, a garnet‐type Li‐ion ceramic electrolyte, and Mo additive, is designed to overcome these obstacles. Different from conventional battery reaction mechanisms, this battery revolutionarily synchronizes the reversible Fe−Mo alloying−dealloying reactions with the delithiation−lithiation processes, meaning that the porous Mo framework derived from Fe−Mo alloy simultaneously suppresses the growth of pure Fe particles. By adopting a Li anode and a Li‐ion ceramic electrolyte, the corrosion problem between the cathode and the solid electrolyte is overcome. With similar battery cost ($12 kWh −1 ), the theoretical energy density of Li−Mo−FeCl2 battery surpasses that of a Na−FeCl2 ZEBRA battery over 25%, to 576 Wh kg −1 and 2216 Wh L −1, respectively. Experimental results further prove this cell has excellent cycling performance (472 mAh gLiCl −1 after 300 cycles, 50 mg active material) and strong tolerance against the overcharge−overdischarge (3−1.6 V) and freezing−thawing (25−250 °C) incidents. Abstract : A garnet‐type Li6.4 La3 Zr1.4 Ta0.6 O12 solid‐electrolyte‐based molten lithium−molybdenum−iron(II) chloride battery is reported. Different from the conventional reaction mechanism of batteries, this battery synchronizes the reversible Fe−Mo alloying−dealloying reactions with the delithiation−lithiation processes, meaning that the porous Mo skeleton derived from the dealloy reaction can suppress the growth of pure Fe particles. This approach is promising for other alkali‐metal−metal‐chloride battery systems.